KINERJA CAMAT DALAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Randi Mandala Putra; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Performance Subdistric Head at empowerment community at Mandah Subdistric faced with problem, wherever Mandah Subdistric region with condition geographical be an area islands still faced various problem for support programme-programme empowerment will be implementation, it problem among others is empowerment community activity doesn’t good enough like PKK, UED-SP and young organization in building programme. That can identified from it hasn’t activity at the office.In this research used performance concept teory from Torang (2003), performance is quality and quantity outcome from individual or groups in organization on implementation principal duty guided by norm, standard operating procedures, criteria and standart a predetermined or apply at organization. Duties and functions Subdistric Head on coordinating empowerment activity that is supporting community participation for joining with planning and building at the area. Do founding and controling to all unit work from goverment programme or empowerment community activity at the area, and also doing evaluation to all empowerment community activity.This research point out that at operate performance subdistric head is limited at programme-programme empowerment has planned from subdistric head office Mandah. But at programme-programme empowerment at subdistric is not optimal yet. Wherever subdistric head skills and coordination on empowerment activity goverment agency and subdistric head is low.Key Words: Performance, Empowerment Community , Coodination